Understanding Rational Numbers : Are the Textbooks helping? - ANDREW, SONA V. (THE PRIMARY TEACHER, 2016)
Classroom discussions with students of pre-service elementary education programme (B El ED2) on the concept of rational numbers has made me reflect on their understanding of rational numbers. During one of the discussions with third-year B El ED students, I asked them what is a rational number? The students gave me the definition of rational number that they had learnt in school. They said, “A rational number is any number in the form a/b, where b≠0”, while “an irrational number is a number that cannot be expressed in the form a/b, where b≠0”